The Influence of Financial Performance, Profit Growth and Company Size on Company Value - YONANDA, Laura Arvioreta; NUGROHO, Hendarto Setiabudi (Journal of Governance, Taxation and Auditing, 2025)
The telecommunications industry in Indonesia faces intense competition, rapid technological advancements, and dynamic changes in consumer needs. Companies in this sector are required to maintain financial performance, optimize profit growth, and manage firm size efficiently to sustain and enhance their firm value. Key challenges include market pressure, demands for innovation, proper asset management, and revenue fluctuations that may influence investor perception. This study aims to analyze the effect of financial performance, profit growth, and firm size on firm value in the telecommunications sector listed on the Indonesia Stock Exchange (IDX)for the 2021-2024 period. The research applies a quantitative approach using secondary data from the annual financial statements of PT Telekomunikasi Indonesia Tbk, PT Indosat Tbk, PT XL Axiata Tbk, and PT Bakrie Telecom Tbk. Data were analyzed using multiple regression tests, t-tests, f-tests, and classical assumption tests with the help of SPSS software. The results indicate that the three variables have no partial effect on firm value; however, they simultaneously have a significant effect, contributing 88,1% to firm value variation.